Optimizing in vitro fertilization in four Caribbean coral species - Valérie F. Chamberland; Matthew-James Bennett; Tania Doblado Speck; Kelly R. W. Latijnhouwers; Margaret W. Miller (PeerJ)
Background Larval propagation and seeding of scleractinian corals for restoration is a rapidly expanding field, with demonstrated applications to assist the recovery of declining populations on reefs. The process typically involves collecting coral reproductive material, facilitating in vitro fertilization (IVF), and settling and outplanting the resulting coral offspring. Optimizing IVF can reduce gamete wastage and increase larval yields for propagation, therefore improving the efficiency of this intervention. Methods In this study we tested three IVF conditions in four Caribbean broadcast-spawning coral species (i.e., Diploria labyrinthiformis, Colpophyllia natans, Pseudodiploria strigosa, Orbicella faveolata) to determine sperm concentration, gamete age, and co-incubation time resulting in the highest fertilization success. For each species, we exposed eggs from a single dam to pooled sperm samples from three sires (1) at concentrations ranging from zero to 109 cell mL−1, (2) after letting gametes age for 2 to 6 h, and (3) for a period of 15 to 120 min. Results These experiments revealed a gamete longevity of at least 4 h and clear minimum sperm concentration thresholds (>105 to 106 cell mL−1) in all four species. Fertilization took place much faster than expected (≤15 min) in the three brain corals under study, whereas O. faveolata gametes required a co-incubation period of 60 to 120 min to achieve maximum IVF success. Discussion We present these results in the context of IVF data available for other hermaphroditic broadcast-spawning scleractinians. We then provide recommendations for coral breeding practitioners to maximize larval production from gamete collections, and finally, we discuss our findings’ potential implications on fertilization dynamics during natural coral spawning events.